The passive ambient comfort and design integration feasibility of vernacular devices in arid housing. (30th September 2019) - Berghout, Belkacem; Forgues, Daniel
The excessive energy consumption in arid climates raises the question of utilising climate's intrinsic adaptive methods which could significantly contribute to energy saving strategies. This article introduces the feasibility of incorporating vernacular device strategies to reduce energy consumption and thereby to more realistically assess the opportunities for adapting these strategies in arid areas. The objective is to develop an overall process focused on the integration of vernacular devices and to realise an effective return for both users and developers by improving energy efficiency. A complexity analysis of the integration of the energetic aspects in several vernacular cases was performed in order to propose design processes that optimise energy performance while ensuring occupants' comfort, based on the proposed building structure morphology. The results concretely illustrate both the interrelation between energy consumption and the various conception choices, and how vernacular devices can condition local energy practices.